Determinants of Rural Residential Solid Waste Collection Services in Lagos State - Olowa, Olatomide W (International Journal of Sustainable Development & World Policy, 2018)
In the wake of increased investment in and new policies regarding Residential Solid Waste Management (RSWM) in Lagos state and the attendant consequence of inefficiencies currently observed with the system, this study describe the state and determinants of waste management services in rural Lagos State. A well-structured questionnaire, which consist of two sections, was used to elicit demographic and residential solid waste collection information from 200 household heads sampled using the multi-stage sampling in 3 Local Council Development Areas (LCDAs). Data were analysed using both descriptive and Dprobit, an advanced probit logistic model. Results show that the mean and standard deviation for whether a ward/neighborhood has RSW collector was 0.23 and 0.42. Similarly, mean and standard deviation for Private Sector Participation (PSP) operator employing RSWC workers was 0.22 and 0.41. Among demographic and residential solid waste collection characteristics, income, population, PSP charges or rates and distance to dump site are found to be determinants of RSWC services in rural areas of Lagos state. The analysis shows that a one thousand increase in Mean income would increase the possibility of providing waste Transportation services by 0.20 percent and the possibility of employing waste workers by only 0.17 percent. Conversely, a one Kilometre increase in distance to dumpsite would reduce the possibility of PSP operator acquiring a compactor. Government incentivisation of rural residential solid waste collection would go a long way to eliminate poor RSWC in rural areas of Lagos State.